Implementasi Kebijakan Keterbukaan Informasi Haji Umrah Di Kantor Kementerian Agama Kota Palembang 2021-2022 - Seftiroyani, Henny; Kencana, Novia; Amaliatulwalidain, Amaliatulwalidain (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2022)
Information has become a necessity that is very much needed by the community, including in the field of public services, which means that people have the right to freedom of information. Therefore, information disclosure policy is very important to be implemented in a government institution. This study aims to find out how the implementation of information disclosure policies and to find out what are the obstacles in implementing information disclosure policies at the Ministry of Religion of Palembang City. This type of research uses qualitative research methods starting from data collection by means of observation, interviews, questionnaires and documentation. The results of this study indicate that the implementation of the Hajj and Umrah information disclosure policy at the Ministry of Religion of Palembang City 2021-2022 has gone quite well, but is still not optimal. There are still problems that occur such as still limited human resources and inadequate infrastructure in carrying out information disclosure policies. The Palembang City Ministry of Religion must optimize human resources, by increasing the number of information and documentation management employees in the information service department and optimizing facilities and infrastructure such as computers, and starting to move to utilize e-government technology by activating the personal website of the Palembang City Ministry of Religion.